Remodeling tumor immunosuppressive microenvironment through dual activation of immunogenic panoptosis and ferroptosis by H2S-amplified nanoformulation to enhance cancer immunotherapy - Yingli Luo; Maoyuan Linghu; Xianyu Luo; Dongdong Li; Jilong Wang; Shaojun Peng; Yinchu Ma (Acta Pharmaceutica Sinica B)
The deficiency in immunogenicity and the presence of immunosuppression within the tumor microenvironment significantly hindered the efficacy of immunotherapy. Consequently, a nanoformulation containing metal sulfide of FeS and GSDMD plasmid (NPFeS/GD) had been developed to effectively augment antitumor immune responses through dual activation of immunogenic PANoptosis and ferroptosis, as well as reprogramming immunosuppressive effects via H2S amplification. The bioactive NPFeS/GD exhibited controlled release of GSDMD plasmid, H2S, and Fe2+ in response to the tumor microenvironment. Fe2+, H2S, and the expression of GSDMD protein could effectively elicit highly immunogenic PANoptosis and ferroptosis. Furthermore, releasing H2S could mitigate the overexpression of indoleamine 2,3-dioxygenase1 (IDO1) induced by immunogenic PANoptotic and ferroptotic cell death and disrupt the activity of IDO1. Consequently, NPFeS/GD effectively triggered the antitumor innate and adaptive immune responses through induction of PANoptotic and ferroptotic cell death and reshaped the tumor immunosuppressive microenvironment to enhance antitumor immunotherapy for metastasis inhibition. This study unveiled the significant potential of immunogenic PANoptosis and ferroptosis in H2S gas therapy for enhancing tumor immunotherapy, offering novel insights and ideas for the rational design of nanomedicine to enhance tumor immunogenicity while reprogramming the tumor immunosuppressive microenvironment.